Performance of Parallel Computing in Bubble Sort Algorithm - Rihartanto Rihartanto; Arief Susanto; Ansar Rizal (Institute of Advanced Engineering and Science, 2017)
The performance of an algorithm can be improved by using a parallel computing programming approach. In this study, the performance of bubble sort algorithm on various computer specifications has been applied. Experimental results have shown that parallel computing programming can save significant time performance by 61%-65% compared to serial computing programming.